The Effect of Jigsaw Strategy on Learning Spiking in Volleyball for Sophomore Students - Amir, Mahir; Khaleel , Riyadh (Journal of Physical Education, 2022)
The research aimed at designing teaching program using jigsaw in learning spiking in volleyball as well as identifying the effect of these exercises on learning spring in volleyball. The researchers used the experimental method on (25) students as experimental group and (27) students as controlling group and (15) students as pilot study group.  The researchers conducted spiking tests then the data was collected and treated using proper statistical operations to conclude that the strategy have a positive effect in experimental group. Finally, the researchers recommended using the strategy in making similar studies on other subjects and skills.